“ENHANCING LEARNING IN DESCRIPTIVE GEOMETRY AND ENGINEERING GRAPHICS THROUGH PEDAGOGICAL INNOVATIONS AND DIGITAL TOOLS” - Shodiev Furqat Davranovich (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores the methods of enhancing teaching and learning in “Descriptive Geometry and Engineering Graphics” at higher education institutions by integrating pedagogical innovations and digital tools. The study focuses on improving students’ spatial reasoning, technical drawing skills, and problem-solving abilities through interactive methods, CAD software, and visual learning aids. The article highlights the advantages of combining traditional teaching strategies with digital technologies to increase engagement, knowledge retention, and professional preparedness.